Models of Consent to Return of Incidental Findings in Genomic Research - Appelbaum, Paul S. (The Hastings Center report, 2014)
Genomic research—including whole genome sequencing and whole exome sequencing—has a growing presence in contemporary biomedical investigation. The capacity of sequencing techniques to generate results that go beyond the primary aims of the research—historically referred to as “incidental findings”—has generated considerable discussion as to how this information should be handled—that is, whether incidental results should be returned, and if so, which ones.Federal regulations governing most human subjects research in the United States require the disclosure of “the procedures to be followed” in the research as part of the informed consent process. It seems reasonable to assume—and indeed, many commentators have concluded—that genomic investigators will be expected to inform participants about, among other procedures, the prospect that incidental findings will become available and the mechanisms for dealing with them. Investigators, most of whom will not have dealt with these issues before, will face considerable challenges in framing meaningful disclosures for research participants.To help in this task, we undertook to identify the elements that should be included in the informed consent process related to incidental findings. We did this by surveying a large number of genomic researchers (n = 241) and by conducting in-depth interviews with a smaller number of researchers (n = 28) and genomic research participants (n = 20). Based on these findings, it seems clear to us that routine approaches to informed consent are not likely to be effective in genomic research in which the prospect of incidental findings exists. Ensuring that participants’ decisions are informed and meaningful will require innovative approaches to dealing with the consent issue. We have identified four prototypical models of a consent process for return of incidental findings.